El debate sobre el aborto en una sociedad democrática : un argumento liberal - Montero, Julio (2017)
In this article I argue that when we discuss about abortion regulations in the context of democratic societies, we must leave aside the issue of whether abortion is morally permissible and focus, instead, on the political issue of whether a democratic State may legitimately punish those women who decide to terminate their pregnancy. This is so because given the fact of pluralism, grounding a law on this subject-matter on private and controversial ethical convictions infringes the principle of democratic legitimacy. Along the same lines, I also argue that once this perspective is adopted, the criminalization of abortion becomes hard to justify as it compromises the right of women to bodily integrity and their equal status as citizens.